Serological and bacteriological evaluation of Salmonella status in swine herds - František Šišák; Hana Havlíčková; Ján Matiašovic; Renata Karpíšková (Czech Journal of Food Sciences, 2011)
The sera from 690 slaughtered fattening pigs from 15 farrow-to-finish swine herds (12 herds of unknown Salmonella status, 3 herds known as latently infected) in the Czech Republic were examined for Salmonella antibodies in a cross sectional study using an ELISA test. Salmonella seroprevalence ranging from 0% to 20% was found in 14 herds. Seroprevalence of 73.9 was found in 1 herd with previously unknown Salmonella status. A longitudinal study of the three previously identified latently infected herds found seroprevalence ranging from 23.9% to 83.4% in sows after farrowing. Salmonella findings from faeces in the farrowing sections ranged between 1.8 and 24.5, and in the environmental samples between 0 and 25. In weaned piglets, Salmonella findings from faeces ranged from 6.3 to 48.0, and in environmental samples from 0 to 90%. The most prevalent serotypes were S. Derby (56.8) and S. Typhimurium, phage type DT104 (18.5). The seroprevalence comparison in sows and slaughtered fattening pigs revealed variations in the course of Salmonella infection in swine herds.